(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Atherosclerosis and plaque formation are driven by inflammation, with high sensitivity C – reactive protein (hs-CRP) serving as a key biomarker of this process and a predictor of coronary heart disease risk. Ischemia occurs when atherosclerotic narrowing limits blood flow, and single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) plays a crucial role in detecting perfusion defects. MPI can distinguish viable from scarred tissue and link the functional impact of atherosclerosis to inflammatory activity in patients with stable ischemic heart disease (SIHD). The study was conducted at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS) between February 2024 to July 2025 with the objective to analyze the correlation between hs-CRP levels and MPI in patients with SIHD. A total of 50 patients with SIHD were selected for SPECT MPI through a single-day stress–(pharmacological) rest protocol. Serum hs-CRP level was measured within one week of SPECT MPI by nephelometry method. The mean age of the participants was 55.2 ± 9.9 years, with a male predominance (76.0%). Hypertension (76.0%) and Diabetes Mellitus (62.0%) were the most common associated risk factors. The mean SSS, SRS, and SDS were 12.4 ± 8.1, 6.5 ± 6.0, and 6.4 ± 2.4, respectively, indicating moderate to severe ischemia. Elevated hs-CRP (>3 mg/L) was found in 38.0% of cases. hs-CRP showed strong positive correlations with SSS (r = 0.657, p < 0.001) and SDS (r = 0.528, p < 0.001), and a moderate positive correlation with SRS (r = 0.479, p < 0.001). These findings indicate that higher hs-CRP levels were closely linked to increased ischemic burden and reduced myocardial function. Therefore, combined assessment of hs-CRP and MPI may improve risk stratification in stable ischemic heart disease. Bangladesh J. Nuclear Med. 28(2): 233-240, July 2025